The improvisational technique of Wes Montgomery on Smokin’ at the Half Note - Matsune, Darryl (Kansas State University, 2023)
Wes Montgomery is one of the most influential guitarists that continues to inspire the generations of musicians that followed his career. Alongside guitarists like Charlie Christian and Django Reinhardt, Montgomery’s innovations constituted him as one of the godfathers in the jazz guitar world. His improvisational solos on the critically acclaimed album, Smokin’ at the Half note, shows Montgomery and The Wynton Kelly Trio at the pinnacle of their musical abilities. This study provides a biography of Wes Montgomery and the history of Smokin’ at the Half Note. Interviews from Montgomery, jazz critics, and his peers of the time show the peaks and valleys that Montgomery endured to become a jazz guitar icon. Furthermore, there is an analyzation of his solos on the album that highlights the use of his three-tiered improvisational approach. The review contains Montgomery’s rhythmic, melodic, and harmonic methods that encompass all three tiers in his improvisations. The ideas in his solos directly translate to the comprehension of the Hard bop styles that stemmed from swing bands and Bebop groups. Additionally, there are written examples that show his techniques on the guitar such as chord voicings, scales, and physical techniques. Included are Montgomery’s fingerings and theoretical concepts that are utilized by all jazz musicians.
Keywords: Wes Montgomery; Smokin' at the Half Note; Jazz guitar; Jazz improvisation